Deciphering the Mode of Action of the Synthetic Antimicrobial Peptide Bac8c - Spindler, E. C. (American Society for Microbiology (ASM), 2011)
Bac8c (RIWVIWRR-NH(2)) is an 8-amino-acid peptide derived from Bac2A (RLARIVVIRVAR-NH(2)), a C3A/C11A variant of the naturally occurring bovine peptide, bactenecin (also known as bovine dodecapeptide), the smallest peptide with activity against a range of pathogenic Gram-positive and Gram-negative bacteria, as well as yeast. The effects of Bac8c on Escherichia coli were examined by studying its bacteriostatic and bactericidal properties, demonstrating its effects on proton motive force generation, and visually analyzing (via transmission electron microscopy) its effects on cells at different concentrations, in order to probe the complexities of the mechanism of action of Bac8c. Results were consistent with a two-stage model for the Bac8c mode of action. At sublethal concentrations (3 μg/ml), Bac8c addition resulted in transient membrane destabilization and metabolic imbalances, which appeared to be linked to inhibition of respiratory function. Although sublethal concentrations resulted in deleterious downstream events, such as methylglyoxal formation and free radical generation, native E. coli defense systems were sufficient for full recovery within 2 h. In contrast, at the minimal bactericidal concentration (6 μg/ml), Bac8c substantially but incompletely depolarized the cytoplasmic membrane within 5 min and disrupted electron transport, which in turn resulted in partial membrane permeabilization and cell death.